The relationship between combined index of triglyceride-waist circumference in the first trimester and incidence of gestational diabetes - Sedigheh Nouhjah; Roya Varzandeh; Leila Moradi; Ferdos Zaman; Zahra Farhangian; Seyed Mahmoud Latifi (Mashhad University of Medical Sciences, 2023)
Introduction: Gestational diabetes is the strongest predictor of diabetes in the future. This study was performed aimed to determine the association between the Hypertriglyceridemic waist phenotype of first trimester and the incidence of gestational diabetes. Methods: This case-control study was designed using the data of gestational diabetes outcomes cohort study. Among 9630 screened mothers in cohort study, 260 women with GDM and 260 healthy pregnant women were compared in terms of clinical, biochemical, and demographic indicators. Gestational diabetes (GDM) was defined by the International Association of Diabetes and Pregnancy Study Group (IADPSG) criteria. Waist circumference and triglyceride levels of all mothers were measured in the first trimester of pregnancy. Data were analyzed by SPSS software (version 23) and Chi-square tests, independent t, univariate and multivariate regression. P<0.05 was considered statistically significant. Results: According to Logistic regression results, the incidence of gestational diabetes was not significantly associated with triglycerides above 150 mg/dL (OR = 1.03 (0.95% CI: 0.52-2.04, P= 0.91)). Waist circumference above 85 cm was associated with a higher risk of developing GDM (OR = 1.72 (0.95% CI: 1.17-2.53, P = 0.005)). The risk of GDM occurrence in mothers with a waist circumference of more than 85 cm and a triglyceride greater than 150 mg /dL was more than the two indicators alone (OR = 3.21 (0.95% CI: 1.71-6.03, P<0.001). Conclusion: The combined index of triglyceride and waist circumference of pregnant women in the first trimester of pregnancy is a relatively good indicator for predicting gestational diabetes.